Plant-Derived Drug Discovery: Introduction to Recent Approaches - Goel B.; Sahu B.; Jain S.K. (My University, 2025)
Drug discovery using plants is an emerging task for leads identification. The drug discovery process involves selection of plant material to phytochemical analysis, characterization, and pharmacological investigation followed by detailed preclinical investigation to clinical trials. Up to 1996, approximately 80% of medicinal products were either directly originated from naturally occurring compounds or motivated by a natural product. 1881 new drugs were approved between the years 1981 and 2019, out of them approximately 23.5% were natural products or semisynthetic derivatives of natural products, and approximately 25% were either natural product mimic or contained pharmacophore from a natural product. Drug discovery requires the development of efficient and feasible leads, which advance from screening a hit to a drug candidate through structural elucidation identification by GC-MS, NMR, IR, HPLC, and HPTLC. The development of new expertise has modernized the evaluation of natural products in new drug discovery. © The Editor(s) (if applicable) and The Author(s), under exclusive licence to Springer Nature Singapore Pte Ltd. 2020.